CEO CHARACTERISTICS AND OPTIMISTIC TONE IN NARRATIVE DISCLOSURE - Varissa, Selvana; Rahman, Annisaa (Widya Mandala Surabaya Catholic University, 2025)
Research Purposes. This study examines the effect of CEO characteristics, namely age, gender, financial expertise, and narcissism, on optimistic tone in the board of directors’ reports of companies listed on the Indonesia Stock Exchange (IDX) in 2022. Research Methods. Using a quantitative approach, this study analyzed data from all companies listed on the IDX with a purposive sampling technique, which resulted in 707 companies as samples and was analyzed using multiple linear regression analysis. Research Results and Findings. The results show that CEO age has a significant negative effect, while CEO narcissism has a significant positive effect on optimistic tone. Contrary to the initial hypothesis, this study finds that companies with female CEOs have a positive and significant impact on the optimistic tone in the board of directors’ reports. The CEO's financial expertise has a positive effect, but an insignificant correlation. The findings support the upper echelons theory, asserting that CEOs' characteristics influence the strategic communication style in corporate reports. This study contributes to the literature on narrative tone in emerging markets and the relevance of CEO characteristics in narrative report preparation.